Design and Operation of Oil Discharge Systems and Characteristics of Oil Used in the Baffin Island Oil Spill Project - Dickins, David F.; Thornton, David E.; Cretney, Walter J. (ARCTIC, 1987)
As part of the Baffin Island Oil Spill (BIOS) Project, two experimental oil discharges were made into bays at Cape Hatt at the northern end of Baffin Island. The objective was to allow the comparison of the nearshore fate and effects of an untreated surface oil slick and oil chemically dispersed into the water column. Weathered Lagomedio crude oil (15 cu m) was discharged onto the water surface in one bay, and most of the slick became stranded on the intertidal zone under the influence of an onshore wind and ebb tide. The oil thickness averaged about 1 mm on the beach face. The same volume and type of oil premixed with Corexit 9527 in a ratio of 10:1 was pumped into a second bay through a perforated diffuser pipe lying on the bottom sediments. The cloud of chemically dispersed oil contacted the bottom sediments and benthic organisms in the second bay and an adjacent third bay. The total exposure in the water column in the second bay was about 300 micro g/g/h and about 30 micro g/g/h in the third bay.Key words: BIOS Project, oil spill, Arctic, oil discharge system, dispersant Mots clés: projet BIOS, déversement de pétrole, Arctique, système de déversement de pétrole, agent de dispersion